Optical spherical electroosmotic phase and optical energy for spherical a-magnetic fibers - Körpınar, Zeliha; Körpınar, Talat (Elsevier Gmbh, 2022)
In this paper, we introduce a different concept of optical spherical a-magnetic fibers with some optical conditions in spherical Heisenberg space. Besides, we give some relationships between optical spherical optimistic density and spherical optical energy for Lorentz forces. By using these optical spherical optimistic density, we give some methods to obtain optical spherical electroosmotic phi(a), phi(t), phi(s)-phase. Finally, we give some related optical electroosmotic microfluidics in spherical Heisenberg space.
Keywords: Optical optimistic density; Microfluidics; Optical electroosmotic; Symmetries; Geometric Phases; Berry Phase; Space Curve; Soliton; Polarization; Rotation; Field